Scalable Fabrication of Crystalline COF Membranes from Amorphous Polymeric Membranes. (9th July 2021) - Fan, Chunyang; Wu, Hong; Guan, Jingyuan; You, Xinda; Yang, Chao; Wang, Xiaoyao; Cao, Li; Shi, Benbing; Peng, Quan; Kong, Yan; Wu, Yingzhen; Khan, Niaz Ali; et al.
Abstract: Covalent organic framework (COF) membranes hold potential for widespread applicability, but scalable fabrication is challenging. Here, we demonstrate the disorder‐to‐order transformation from amorphous polymeric membrane to crystalline COF membrane via monomer exchange. Solution processing is used to prepare amorphous membrane and the replacing monomer is selected based on the chemical and thermodynamical stability of the final framework. Reversible imine bonds allow the extraneous monomers to replace the pristine monomers within amorphous membrane, driving the transformation from disordered network to ordered framework. Incorporation of intramolecular hydrogen bonds enables the crystalline COF to imprint the amorphous membrane morphology. The COF membranes harvest proton conductivity up to 0.53 S cm −1 at 80 °C. Our strategy bridges amorphous polymeric and crystalline COF membranes for large‐scale fabrication of COF membranes and affords guidance on materials processing. Abstract : A disorder‐to‐order transformation strategy is developed for the scalable fabrication of highly crystalline covalent organic framework (COF) membranes from amorphous polymeric membranes via monomer exchange.